Penerapan Strategi Pembelajaran Kooperatif Model Jigsaw untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SDN 46 Buton Kecamatan Lasalimu Kabupaten Buton - Fajrianti Fajrianti; Sitti Hermayanti Kaif; Aisha Wunasari; Zumiati Zumiati (Universitas Negeri Makassar, 2022)
This application was prepared with the aim to remind the ips learning outcomes of students of grade IV SDN 46 Buton through the application of cooperative learning strategies jigsaw model. The learning outcomes referred to in this study are ips learning outcomes. The type of research that is in the study is PTK. This research was conducted in the even semester of the 2021//2022 school year. The study subjects were students of grade IV SDN 46 Buton which amounted to 16 students. Data collection techniques use observations, tests, and documentation. Data analysis techniques are data reduction, data presentation, and conclusion withdrawal. The results showed an increase in the IPS learning outcomes of students in grade IV SDN 46 Buton, namely in the cycle by 66.66% (sufficient category), then in cycle II increased by 75% (good category). This is an increase of 8.34%. Thus the application of cooperative learning strategies jigsaw model can improve the ips learning outcomes of students of grade IV SDN 46 Buton